2008
DOI: 10.1007/s00417-008-1012-3
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain measured at 6 weeks after birth as a predictor for severe retinopathy of prematurity: study with 317 very low birth weight preterm babies

Abstract: Low WG by six weeks of life is an important and independent risk factor for severe ROP and is capable to predict the development of severe ROP in most patients that needed treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 30 publications
2
43
0
8
Order By: Relevance
“…Currently, low weight gain after premature birth is widely accepted as a predictive factor for later development of ROP, being considered superior to BW and GA alone as predictors. [12][13][14][15][16][17][18] In addition, ROPScore also takes into account the use of oxygen in mechanical ventilation and the need for blood transfusions. All these risk factors are involved in the process of ROP development and can be easily identified by ophthalmologists during the initial ROP screening eye examination.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, low weight gain after premature birth is widely accepted as a predictive factor for later development of ROP, being considered superior to BW and GA alone as predictors. [12][13][14][15][16][17][18] In addition, ROPScore also takes into account the use of oxygen in mechanical ventilation and the need for blood transfusions. All these risk factors are involved in the process of ROP development and can be easily identified by ophthalmologists during the initial ROP screening eye examination.…”
Section: Discussionmentioning
confidence: 99%
“…This would allow identifying, in a timely manner, babies at risk of developing severe ROP. Fortes Filho et al (17) , in 2009, demonstrated in a prospective study the practical importance of assessing and monitoring WG in the first 6 weeks of life as a predictive factor for later onset of ROP. In that study, it was reported that the occurrence of WG less than 51.2% of BW in the first 6 weeks of life was indicative for the development of severe ROP.…”
Section: Main Risk Factors For Ropmentioning
confidence: 99%
“…In that study, it was reported that the occurrence of WG less than 51.2% of BW in the first 6 weeks of life was indicative for the development of severe ROP. Since assessing and monitoring WG can be easily performed during screening programs for detection of ROP, and especially because it does not add costs to the public health system of developing countries, this procedure would be of paramount importance as a practical clinical tool for ophthalmologists carrying out screening sessions for detection of ROP (17,18) .…”
Section: Main Risk Factors For Ropmentioning
confidence: 99%
“…While degree of prematurity is decisive, oxygen treatment is the most studied risk factor, which, when poorly controlled, still causes blindness in relatively mature preterm babies. 1 Recently, poor weight gain during the first weeks of life has been found to be strongly associated with later ROP development, [2][3][4] indicating that factors causing impaired general growth also have a negative impact on retinal vessel development.…”
mentioning
confidence: 99%